Enhancing Organizational Commitment through Risk Management: The Moderating Role of Self-Efficacy among SME Employees in Bali - Ni Wayan Lasmi; Wayan Sri Maitri; Komang Widhya Sedana Putra P (Jurnal Ilmu Manajemen dan Bisnis, 2025)
Within any organization, the value of risk management depends on the level of organizational trust, the commitment, and the organizational core functions of financial viability. Still, for small and medium enterprises (SMEs), risk management assignments for the organization value are still seen functionally and technically. This neglects the management control systems from the behavioral and psychological aspects. Consequently, there is minimal scholarship that dissects the interrelations of the human component and organizational systems articulated for commitment and loyalty in the smaller business dimension. To fill this void, the current study utilizes the framing of Behavioral Risk Management Theory with Social Cognitive Theory to assess the relationship of risk management to organizational commitment with self-efficacy as a moderating variable. Quantitative data were acquired using a structured questionnaire and distributed to SME employees in the Bali Province. These data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). It was ascertained that risk management systems function and organizational commitment. Self-efficacy was identified as a significant antecedent influence on organizational commitment. Employees who advanced self-efficacy view risk management systems as organizational supports, access organizational structures, and perceive that organizational trust is extended to them, reinforcing commitment to the organization. This study delineates the need for GRM systems and incorporates psychological risk management systems. Subsequent studies may improve the model by adding variables like perceived organizational support, trust, and leadership style to better capture the human aspects of risk management in maintaining committed employees and resilient organizations.